Establishment of the credit risk database: Concrete use to evaluate the creditworthiness of SMEs - Satoshi Kuwahara; Naoyuki Yoshino; Megumi Sagara; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2019)
The credit risk database (CRD) makes it possible to mitigate the problem of information asymmetry between SMEs and financial institutions and contributes to improving SMEs' access to finance by collecting a large number of financial statements through the mechanism of SME finances and establishing a robust statistical model. In this paper, we use the CRD in Japan, confirm the situation in Japan, and highlight the CRD's contribution to evaluating the creditworthiness of SMEs. We also explain how to establish the CRD as a financial infrastructure, while indicating that the CRD and the scoring model based on it have maintained their quality owing to their operating system. We hope our experience contributes to the introduction of a statistical credit risk database composed of a large number of anonymous financial statement data in other countries and that the CRD helps to improve SMEs' access to finance as a financial infrastructure.
Keywords: G21; G28; G32; 330; credit risk database; CRD creditworthiness; SMEs in Japan